The Transitioning Families Therapeutic Reunification Model in Nonfamilial Abductions. (April 2016) - Judge, Abigail M.; Bailey, Rebecca; Behrman‐Lippert, JoAnn; Bailey, Elizabeth; Psaila, Cynthia; Dickel, Jane
Abstract: The existing literature on abduction reunification is limited and evolving. Although guidelines for model service approaches exist, few programs address the unique challenges of reunifying children and families following abduction. This article delineates a family‐based reunification model that has assisted families affected by abduction since 2006. Model components include a team‐centered approach, a stage‐oriented reunification process, and pitfalls and strategies related to intersystem collaboration. We present the value of a family‐systems, solution‐focused, trauma‐informed, and case‐specific approach to therapeutic reunification following child abduction. Evidence that is contrary to the popular notion of Stockholm's syndrome is also marked. Research on the efficacy of therapeutic reunification is essential for the growth of systems equipped to address the dynamic needs of these families. Accordingly, suggestions for evaluation research are proposed. Key Points for the Family Court Community: Families face a range of unique challenges during reunification following abduction. Historically, therapeutic reunification has emphasized the needs of the central victim with only a perfunctory focus on the family. This article delineates a family‐based reunification model that has assisted families affected by abduction since 2006. We present the value of a family‐system, solution‐focused, trauma‐informed, and case‐specific approach to therapeutic reunification following child abduction.